Analisis Filosofis Tentang, Metode Yesus dan Keterlibatan Jemaat Dalam Penginjilan - Sanherib Boling; B.D. Nainggolan; A Hendrik (Pascasarjana IAKN Manado, 2023)
The purpose of this research is to obtain data about the Yesu method and the involvement of the Congregation in Evangelism. Research in this journal uses literature and observation. Research results show that evangelism is a way to tell people that you care about them, and God cares about them too. As a form of concern for people's safety, evangelism is a must for every follower of Christ, and a sign of your loyalty to Him. That spiritual growth takes place in the company of the redeemed and, on the other hand, as a witness for the group that needs to be redeemed.